Promotion of collagen mineralization and dentin repair by succinates. Issue 30 (25th July 2022) - Jin, Wenjing; Jin, Yeli; Duan, Pengqiang; Wu, Haiyan; Zhang, Leiqing; Du, Qiaolin; Pan, Haihua; Tang, Ruikang; Shao, Changyu
Abstract : We demonstrate that the small biomolecule, SA, could significantly promote collagen mineralization by improving the physicochemical properties of the collagen-mineral interface. Abstract : Biomineralization of collagen fibers is regulated by non-collagenous proteins and small biomolecules, which are essential in bone and teeth formation. In particular, small biomolecules such as succinic acid (SA) exist at a high level in hard tissues, but their role is yet unclear. Here, our work demonstrated that SA could significantly promote intrafibrillar mineralization in two- and three-dimensional collagen models, where the relative mineralization rate was 16 times faster than the control group. Furthermore, the FTIR spectra and isothermal experimental results showed that collagen molecules could interact with SA via a hydrogen bond and that the interaction energy was about 4.35 kJ mol −1 . As expected, the SA-pretreated demineralized dentin obtained full remineralization within two days, whereas it took more than four days in the control group, and their mechanical properties were considerably enhanced compared with those of the demineralized one. The possible mechanism of the promotion effect of SA was ultimately illustrated, with SA modification strengthening the capacity of the collagen matrix to attract more calcium ions, which might create a higher local concentration that could accelerate the mineralization of collagen fibers. These findings not only advance the understanding of the vital role of small biomolecules in collagen biomineralization but also facilitate the development of an effective strategy to repair hard tissues.